ANALISIS VEGETASI Avicennia sp. DAN KARAKTERISTIK SEDIMEN DI KAWASAN MANGROVE DESA SUNGAI RAWA KECAMATAN SUNGAI APIT KABUPATEN SIAK, RIAU - Fadli '; Khairijon '; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The vegetation analysis of Avicennia sp. in Sungai Rawa coastal had been conducted from January to February 2014. This research aimed to determine the species composition, structure, and condition of mangrove vegetation, as well as sediment characteristic. Sampling were conducted at three different station based on purposive sampling method using multilevel plot (Nested Quadrat). The results showed that mangroves species found in the coastal village of Sungai Rawa were Avicennia alba and Avicennia lanata. The level of seedling, saplings and trees showed that A.alba was dominant at three station. Analysis of sediment showed that the substrate within three station were sand and mud. The analysis showed that mud substrate was dominant in all of the reseach site. The corelation betwen the vegetation and substrate showed a positive corelation with mud substrate and negative corelation with sand substrate.